PENGEMBANGAN ANALISA GLIBENKLMID MENGGUNAKAN SORBEN POLIMER BERCETAKAN MOLEKUL - Lasmaryna Sirumapea; Herlina Herlina; Hilma Hilma; Mellinda Mellinda (Universitas Lampung Jl. Prof. Dr. Sumatri Brojonegoro No.1 Bandar Lampung, 2023)
Research on the development of glibenclamide analysis has been carried out using molecularly printed polymeric sorbents. This study aims to prepare a selective and accurate method of determining glibenclamide, through the molecular imprint method. Glibenclamide imprinted polymers have been successfully synthesized. Methyl methacrylic acid, ethyleneglycodimethacrylate, benzoyl peroxide were dissolved in acetonitrile and chloroform at a controlled temperature of 70°C. Extraction was carried out with methanol: acetic acid (8.5:1.5). Physical functional group analysis was carried out with FTIR spectrophotometer which showed specific peaks of glibenclamide, amine and amide groups at 3405 cm-1. The selectivity test gave the following results: imprinting factor (IF) = 2.45 and the selectivity coefficient (λ) for ramipril = 1.21 and against metformin = 2.28. The results showed that the polymer had a good impression and was selective for glibenclamide analysis Keywords: glibenklamid, molecularly imprinted polymer, metformin, ramipril.